To Intubate or Not: A Comprehensive Clinical Analysis of Airway Management and Stabilization Strategies for Neonatal Congenital Diaphragmatic Hernia in Resource-Limited Facilities - Ida Ayu Sintya Pratiwi; I Wayan Dharma Artana (The International Journal of Medical Science and Health Research, 2025)
Introduction: Congenital Diaphragmatic Hernia (CDH) remains a formidable challenge in neonatal medicine, particularly in low- and middle-income countries (LMICs) where diagnostic resources and advanced life support modalities, such as extracorporeal membrane oxygenation (ECMO), are often unavailable.1 This condition, characterized by the herniation of abdominal viscera into the thoracic cavity through a diaphragmatic defect, leads to a critical triad of pulmonary hypoplasia, persistent pulmonary hypertension of the newborn (PPHN), and cardiac dysfunction.3 The immediate postnatal management, specifically the decision to initiate invasive mechanical ventilation versus non-invasive support, is a pivotal determinant of survival.3 Case Illustration: This report details two distinct cases of postnatally diagnosed CDH at a Type C hospital in Bali, Indonesia. Case 1 involves a full-term female neonate (2,900g) presenting with moderate respiratory distress (Apgar 4/5/6), who was successfully stabilized using non-invasive continuous positive airway pressure (CPAP) and orogastric decompression before being referred at 20 hours of life. Case 2 involves a full-term low-birth-weight female neonate (2,325g) with prenatally suspected dextrocardia and severe hypoxemia (SpO2 40%), necessitating prompt endotracheal intubation and pressure-controlled ventilation to achieve physiological stability prior to tertiary referral. Discussion: The analysis explores the embryological origins of the diaphragmatic defect, occurring between the 4th and 12th weeks of gestation, and the physiological impact on lung development.3 It highlights the utility of the Downes score for clinical monitoring in settings where arterial blood gas analysis may be limited.6 Furthermore, the discussion contrasts the "gentle ventilation" strategy with historical hyperventilation approaches and examines the systemic challenges of neonatal transport within the Indonesian healthcare framework.7 Conclusion: Individualized airway management is essential in resource-limited settings. While immediate intubation is mandatory for severe hypoxemia, non-invasive stabilization may be appropriate for clinically stable phenotypes, provided meticulous orogastric decompression is maintained.3 Early recognition and standardized referral pathways are critical to improving survival outcomes in these complex cases.9